Pengaruh Penambahan Ekstrak Bunga Mawar terhadap Kualitas Sabun Mandi Berbasis Minyak Kelapa - Maripa, Baiq Risni; Ahmadi, Ahmadi (Indonesian Journal of STEM Education, 2023)
Bath soap is a hygiene product widely used by the public, with demand for safe, high-quality natural soaps continuing to rise. This study aims to analyze the effect of adding rose flower extract (Rosa damascena Mill.) on the quality of coconut oil-based bath soap, as assessed by physicochemical and organoleptic parameters. The experimental study employed a completely randomized design with four treatments of rose flower extract concentrations: 0% (control), 3%, 6%, and 9%, each with three replicates. The soap was produced via the cold saponification method using coconut oil as the base material, with the addition of sodium hydroxide, distilled water, and rose flower extract obtained through maceration in 70% ethanol for 3×24 hours. The quality parameters tested included pH, moisture content, foam height, foam stability, homogeneity, texture, color, aroma, and panelist acceptance. Data were analyzed using one-way ANOVA and Duncan’s post-hoc test at a significance level of ?=0.05. The results showed that the addition of rose flower extract significantly affected all soap quality parameters (p<0.05). The treatment with a 6% concentration produced soap with optimal quality: pH 9.2 ± 0.3, moisture content 18.4 ± 1.2%, foam height 8.6 ± 0.4 cm, foam stability 82.3 ± 2.1%, excellent homogeneity, soft texture, attractive pink color, strong characteristic rose aroma, and the highest panelist acceptance (score 4.2 ± 0.3 on a 5-point scale). A higher extract concentration (9%) resulted in a hard texture and an overly dark color, which the panelists found less appealing. Coconut oil-based bath soap with 6% rose flower extract meets the SNI 06-3532-2016 standard and has the potential to serve as a high-quality natural soap alternative with added aesthetic and aromatherapeutic value.